Migration Between Two Inverse Time-Overcurrent Curves of Different Standard: Experience at Siguragura Power Station - Bagus Brahmantya Gautama (Jurusan Teknik Elektro Universitas Andalas, 2019)
The inevitable replacement of electro-mechanical protection relays with more recently-developed microprocessor-based protection relays poses challenges to engineer, one of which is migration from existing manufacturer’s non-standard inverse time-overcurrent curve to, usually, IEC 60255-151 or IEEE Std C37.112-1996 curve. To satisfy the required protection coordination, one may perform new study of protection coordination for the system in total, prior to replacement program. However, this exhaustive approach can be avoided by emulating existing non-standard inverse time overcurrent curve on the new microprocessor-based protection relay, provided that such curve is still adequate to be re-implemented. This paper aims to develop general procedure using nonlinear curve fitting to determine the most appropriate setting of microprocessor-based protection relay. The general procedure has been tested during renewal of feeder protection relay at Siguragura Power Station.